mauriciodiazxcv
mauriciodiazxcv
04-05-2018
Mathematics
contestada
6q + q − 3q − 1 = 11 q =
Respuesta :
MiNk2019314
MiNk2019314
04-05-2018
Use algebra to solve for q:
6q+q-3q-1=11q
4q-1=11q
-1=7q
q=-1/7
Answer Link
VER TODAS LAS RESPUESTAS ( 97+ )
Otras preguntas
The electric force between two charges increases when A) both charges become negative B) both charges become positive C) the charges get closer together D) the
two perpendicular lines have the same y-intercept. if the equation of one of those lines is y=0.5x - 1, what is the equation of the other line?
¿Qué documento sirvió de base para la rebelión contra Boyer? * La Constitución La Reforma El Código Rural
Please help and hurry!
Based on your knowledge of roots and affixes, which is the most likely definition for the word circumnavigate?
When she learned that she could not attend the university in Warsaw, she felt
math math math math math
Write an inequality, in slope-intercept form, for the graph below. If necessary, use '<="for < or ">" for >. (-3,0) X 5 (0, -3) -5
Select the correct answer. Which formula below will return the same result as the formula =SUM(B1:B5)? A. =B1+B5 B. =B1+B2+B3+B4+B5 C. =B1,B2,B3,B4,B5 D. =B
what is photo synthesis ?